Preparation and Evaluation of Hydrogel Containing Prednisolone Nanoparticles - Walaa A. Saihood; Hayder K. Abbas (College of Pharmacy / Mustansiriyah University, 2023)
Currently, nanoparticles technology is well known and it used to augment the rate of drug dissolution and considerably increased bioavailability. Nanoparticles have been combined with hydrogel to form nanoparticle-hydrogel hybrid system as a substitute to conventional dosage forms. The goal of this study is to prepare an effective hydrogel form containing prednisolone nanoparticles as a hybrid biomaterial system for transdermal application. Six hydrogel formulations containing prednisolone nanoparticles were prepared and characterized for particle size, entrapment efficiency, physical appearance, pH, drug content, spreadability test, viscosity, in-vitro drug release and ex-vivo diffusion. The results showed that the all preparations in the nanometer size and the drug content of prednisolone in hydrogel was ranged from 96.24% to 99.15% and there was a significant enhancement (p<0.05) in drug release and permeation from the prepared nanoparticles -hydrogel formulas when compared with plain hydrogel of prednisolone. From this study, it can be concluded that nanoparticle-hydrogel system could be a possible drug delivery technology for transdermal application of prednisolone drug.